Social work education in Malaysia and Indonesia: history and development - Amin, Samir Muhazzab; Nazuri, Nur Shuhamin; Ahmad Suhaimi, Siti Shazwani (Human Resource Management Academic Research Society, 2022)
This paper gives an overview of the brief history and current situation of social work education between Malaysia and Indonesia. This paper highlights social work education practice, issues, needs, and challenges in those two countries. The issues identified to be regarding the development of social work program in Malaysia and Indonesia includes western influence, professional, colonization, multicultural, and governance issues. The issues and difficulties raised in this paper provide insights to implement further input to develop and improvise social work education programs in Malaysia and Indonesia. Both countries faced similar issues and challenges with social work education programs. However, they also have two separate disputes to overcome. Therefore, it is vital for both countries to work and focus to overcome the problem according to their necessity.